Предмет: Математика, автор: grebenshikova21

Вычислить пределы не используя правило Лопиталя
Распишите пожалуйста

Приложения:

Ответы

Автор ответа: pavlikleon
1
1)
 \lim_{x \to \infty}  \sqrt[6]{ \frac{3 x^{2} +4}{3 x^{2} +x} }  = \\  \\ 
 \lim_{x \to \infty}  \sqrt[6]{ \frac{3 x^{2} +x+4-x}{3 x^{2} +x} }  = \\  \\ 
 \lim_{x \to \infty}  \sqrt[6]{1+ \frac{4-x}{3 x^{2} +x} }  = \\  \\ 
 \lim_{x \to \infty}  \sqrt[6]{1+ \frac{4}{3 x^{2} +x}-\frac{1}{3 x +1} }  =  \sqrt[6]{1+ \frac{4}{\infty}-\frac{1}{-\infty} }=  \sqrt[6]{1+ 0+0 }=1

2)
 \lim_{x \to -2}  \frac{3- \sqrt{11+x}}{2- \sqrt{x+6} } = \\  \\ 
 \lim_{x \to -2}  \frac{(3- \sqrt{11+x})*(2+ \sqrt{x+6})*(3+ \sqrt{11+x})}{(2- \sqrt{x+6}) *(2+ \sqrt{x+6})*(3+ \sqrt{11+x})} = \\  \\ 
 \lim_{x \to -2}  \frac{(3^{2}- (11+x))*(2+ \sqrt{x+6}))}{(2^{2}- (x+6)) *(3+ \sqrt{11+x})} = \\  \\ 
 \lim_{x \to -2}  \frac{(9- 11-x)*(2+ \sqrt{x+6}))}{(4- x-6) *(3+ \sqrt{11+x})} = \\  \\ 
 \lim_{x \to -2}  \frac{(-2-x)*(2+ \sqrt{x+6}))}{(-2- x) *(3+ \sqrt{11+x})} = \\  \\
 \lim_{x \to -2}  \frac{2+ \sqrt{x+6}}{3+ \sqrt{11+x}} = \frac{2+ \sqrt{-2+6}}{3+ \sqrt{11-2}} =  \frac{2+ \sqrt{4}}{3+ \sqrt{9}} = \frac{2+2}{3+3} =\frac{4}{9}



Похожие вопросы